3D didactic model and useful guide of the semicircular conducts - Rivas,Ricardo D'Albora (2011)
Knowledge of the anatomy and physiology of the semicircular canals and their central pathways is essential for the diagnosis of vestibular pathology. This 3 dimensional (3D) scheme of the Semicircular Canals (SSCC) is a teaching tool and a useful reference guide for rapid consultation. MATERIAL AND METHODS: A multicolored cardboard model is accompanied by a user manual which provides a thorough description of the tool for the most common vestibular diseases. RESULTS: Although results cannot be quantitatively assessed, the model has been well received at several Latin American scientific conferences. The model is often understood with verbal instruction only; nevertheless, a printed user manual is included. CONCLUSIONS: This 3 dimensional (3D) model of the Semicircular Canals (SSCC) is a practical, low cost tool for use in private and academic settings.